Analisis penerapan akuntansi manajemen lingkungan pada perusahaan sub sektor kayu dan pengolahannya di Bursa Efek Indonesia (BEI) dan kesesuaiannya dengan Standard Global Reporting Initiative (GRI) - Samosir, Mikhael Ramos; Sondakh, Jullie J.; Tirayoh, Victorina Z. (Riset Akuntansi dan Portofolio Investasi, 2024)
Poor company environmental management requires an Environmental Management Accounting system as environmental control which is used to identify, assess, measure and present waste management costs from operational activities. This research aims to find out whether the application of environmental management accounting in the reporting of manufacturing companies in the wood and processing sub-sector is in accordance with global reporting initiative standards. The method used in this research is a qualitative descriptive approach, so it can be seen whether the environmental management accounting system and sustainability reports of manufacturing companies in the wood and processing sub-sector have been presented properly and correctly. Based on the research results, it can be concluded that 4 companies in the wood sub-sector manufacturing and processing companies listed on the Indonesia Stock Exchange (BEI) are in accordance with the Global Reporting Initiative (GRI) Standard and only one company provides an internal failure environmental cost report.